Ethnomethodology, conversation analysis and constructive analysis : on formal structures of practical action - Button, Graham, 1950-; Lynch, Michael, 1948-; Sharrock, W. W. (Wes W.) (Abingdon, Oxon ; New York, NY : Routledge, 2023)
"This book revisits the arguments by which Harvey Sacks and Harold Garfinkel opposed the widespread attempt in the social sciences to construct disciplinary theories and methods in place of common-sense knowledge of human action, and proposed instead an alternative that would investigate the organised methods of natural language use and common-sense reasoning that constitute social orders - arguments that led to the establishment and proliferation of ethnomethodology and conversation analysis. As the very 'constructive analysis' that they opposed has begun to be incorporated into influential lines of research in ethnomethodology and conversation analysis, the authors return to the founding insights of the field and reiterate the importance of Garfinkel and Sacks' original and controversial proposals for an 'alternate' sociology of practical action and practical reasoning. Showing how constructive analysis has become entrenched in ethnomethodology and conversation analysis and arguing for a need to 're-boot' these approaches, this volume constitutes a call for a renewal of the radical alternative proposed by Garfinkel and Sacks"--
Keywords: Ethnomethodology; Conversation analysis; Discourse analysis; SOCIAL SCIENCE / Methodology; SOCIAL SCIENCE / Research